Pengembangan Media Kartu Kata Bergambar untuk Keterampilan Membaca Permulaan pada Siswa Kelas I SDIT Al-Muthmainnah Jambi - Ayu Wulandari; Umil Muhsinin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop a picture word card learning media to improve early reading skills in first-grade students at SDIT Al-Muthmainnah Jambi. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). During the validation phase, the media received a score of 95% from material experts and 96% from media experts, indicating that it is highly valid. Practicality was tested through teacher responses (100%) and student responses (average 94.4%), while its effectiveness was demonstrated by an average student reading test score of 95%. The results show that this media is highly suitable for use in early reading instruction.